Oral Health Awareness and Practices among Libyan University Students: Insights into Non-Bacterial Tooth Wear - Alfitory Ahmed, Karima; Gehani, Ghada; Mohamed Own, Najwa (Libyan Journal of Dentistry, 2025)
Background: Tooth substance loss, when unrelated to bacterial activity, encompasses several conditions such as attrition, abrasion, erosion, and resorption. Each of these forms of tooth wear results from different etiological factors, including mechanical forces, dietary acids, and physiological processes. Despite the significance of these conditions, awareness of non-bacterial causes of tooth wear is limited among the general population, especially young adults. University students, who are exposed to a variety of stressors and lifestyle habits, may be at increased risk for these issues. Objective: This study investigates the prevalence of non-bacterial tooth substance loss and evaluates the level of awareness among Libyan university students, focusing on factors that contribute to attrition, abrasion, erosion, and resorption. Methods: A cross-sectional study was conducted using an online Google Forms survey, distributed via social media. A total of 523 responses were collected. The questionnaire gathered demographic data, oral health practices, symptoms of non-bacterial tooth substance loss (NBTLS), and awareness of conditions like attrition, abrasion, erosion, and resorption. Descriptive statistics were used to analyze the data, assessing prevalence and awareness levels. Chi-square tests examined associations between demographic factors, oral health habits, and NBTLS awareness. Statistical significance was set at p < 0.05. Results: The study involved 523 Libyan university students, revealing a significant age skew towards 21-23 years (56.8%), with a majority female population (69.8%). Most participants were from the Dental field (62.9%). In terms of oral health practices, 38.2% visited the dentist every six months, and 57.9% brushed twice daily. Awareness of non-bacterial tooth loss conditions varied, with 68.9% recognizing abrasion and 54.1% erosion. Notably, 45.5% reported experiencing tooth wear symptoms, and 99.2% showed strong interest in learning about non-bacterial causes of tooth wear, with a binomial test confirming this interest as statistically significant (p < 0.001). Conclusion: This study underscores a significant awareness of non-bacterial tooth substance loss among Libyan university students, alongside a marked interest in further education on this subject. Despite the generally proactive oral health practices observed, there is variability in awareness of specific conditions such as erosion and resorption. The overwhelmingly high interest in learning about non-bacterial causes of tooth wear, supported by statistical significance, indicates a critical need for enhanced educational initiatives. Targeted interventions are essential to bridge existing knowledge gaps and promote effective preventative strategies within this demographic.